Sehnsucht und Liebe in Lancelot und Ginover - Ponikvar, Carmen Bianca (Vestnik za tuje jezike, 2018)
Longing and love are the main emotions often found in Arthurian romances, and they can have a positive or negative effect on the characters. On the one hand love encourages the knights' will to fight and to serve their ladies in order to win their affection. On the other hand, the knights' separation from their loved ones, or the longing for their love, infuriates them. They become weak, distracted from their fights and eventually fall ill. It is exactly this dualistic aspect of love and longing which is analysed in Prosalancelot, relatingto the love affair of Lancelot and Ginover, and the friendship between Lancelot and Galahot. The analysis will focus on how these emotions affect the characters, and the extent of their influence on their behaviour. Lancelot is a very emotionally driven character due to his extreme love and longing for his queen Ginover, which controls his whole life and influences the way the other characters perceive him.
Keywords: dvorna ljubezen; literarne študije; nemška književnost; Prosalancelot; srednjeveška književnost